Determinants of tenure choice in Japan: What makes you a homeowner? - Toshiaki Aizawa; Matthias Helble (Asian Development Bank Institute (ADBI), 2016)
Despite Japan's highly developed housing market, little is known about the determinants of renter-to-homeowner tenure transition. Exploiting the Japanese longitudinal household data of the Keio Household Panel Survey (2004-2013), this paper aims to close this gap. Our results show that income level and increase in family size are the strongest determinants for homeownership in Japan. We find that although both rural and urban households with higher incomes are more likely to transition to homeownership, access in rural areas is more equally distributed over various income groups. Since most of the previous empirical studies on tenure choice pay little attention to wealth as a measure of purchasing power, possibly due to data limitation, we draw attention to it and its relative levels. We find that household wealth levels matter, particularly in urban areas, whereas in rural areas homeownership is more equally distributed. Nonetheless, given the relatively low levels of household wealth among renters, our results suggest that income is a more important determinant of successful tenure transition.
Keywords: R21; R30; 330; homeownership; housing tenure; tenure choice in Japan; Japanese homeowner